2007
DOI: 10.1016/j.chiabu.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse in the eyes of the beholder: Lay perceptions of child sexual and physical abuse

Abstract: Objective: The purpose was to explore the effects of victim and perpetrator gender, type of abuse, and victim-perpetrator relationship on university students' and non-students' perceptions of different kinds of child abuse. Method: One hundred and ninety-nine participants (including university students and non-student adults) evaluated each of 24 vignettes (within-subjects design) describing an abusive interaction between a child and an adult. The following four variables were manipulated: the victim's gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 36 publications
1
59
1
Order By: Relevance
“…CSA perpetrated by males was seen as more abusive and more severe than CSA done by females (Bornstein, Kaplan & Perry, 2007;. Victims of males were also seen as more credible and more believable in their accounts of CSA .…”
Section: Public Opinion Of Child Sexual Abusementioning
confidence: 91%
See 1 more Smart Citation
“…CSA perpetrated by males was seen as more abusive and more severe than CSA done by females (Bornstein, Kaplan & Perry, 2007;. Victims of males were also seen as more credible and more believable in their accounts of CSA .…”
Section: Public Opinion Of Child Sexual Abusementioning
confidence: 91%
“…Some studies have found that the gender of the victim did not influence perceptions of the CSA (Kennel & Agresti, 1995;Wiley & Bottoms, 2009). However, one study found that the abuse of female children was seen as more traumatic and more severe, though this perception did not influence the believability of these female victims (Bornstein et al, 2007). The discrepancy in perceptions may be a result of different samples, as one study utilized licensed psychologists (Kennel & Agresti, 1995) and the two others utilized a sample of undergraduate students (Bornstein et al, 2007;Wiley & Bottoms, 2009).…”
Section: Public Opinion Of Child Sexual Abusementioning
confidence: 93%
“…Studies of child sexual abuse have demonstrated that the gender of the abuser strongly determines how offenders are perceived, with men viewed more negatively than women (Bornstein et al 2006;Rogers and Davies 2007). The four key studies on perceptions of adult-teen sexual relationships examined how the genders of the adult and teen influenced perceptions.…”
Section: Perceptions Of Adult-teen Sexual Relationshipsmentioning
confidence: 97%
“…Studies found that the victims of the sexual abuse are traumatized greatly in life compared to other types of child abuse [22]. Reference [23] adds that a child who is abused will be traumatized and will need counseling and professional intervention by a child psychologist or psychiatrist.…”
Section: A Literature Reviewmentioning
confidence: 99%